2016
DOI: 10.12659/pjr.895307
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging Features in the Characterization of Non-Growing Solid Pulmonary Nodules in Non-Smokers

Abstract: SummaryBackgroundA disappearing or persistent solid pulmonary nodule is a neglected clinical entity that still poses serious interpretative issues to date. Traditional knowledge deriving from previous reports suggests particular features, such as smooth edges or regular shape, to be significantly associated with benignity. A large number of benign nodules are reported among smokers in lung cancer screening programmes.The aim of this single-center retrospective study was to correlate specific imaging features t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous evidence showed that the size of lesions shown by CT were basically identical with those after surgery, and correlation coefficients on the x-, y- and z-axes were 0.710, 0.944 and 0.875, respectively ( 7 ). SPN diameter may influence the pathological nature of the nodule and corresponding clinical manifestations.…”
Section: Discussionmentioning
confidence: 78%
“…Previous evidence showed that the size of lesions shown by CT were basically identical with those after surgery, and correlation coefficients on the x-, y- and z-axes were 0.710, 0.944 and 0.875, respectively ( 7 ). SPN diameter may influence the pathological nature of the nodule and corresponding clinical manifestations.…”
Section: Discussionmentioning
confidence: 78%